Effectiveness of Community-Based Nutrition Interventions in Preventing Stunting and Malnutrition in Toddlers: A Literature Review - Siti Maria Ladia Paradisa Syitra; Anita Tiara; Abul A'la Tarigan (International Journal Of Health Science, 2025)
Stunting and undernutrition remain serious public health issues among under-five children, particularly in developing countries. Community-based nutrition interventions are considered effective in integrating both specific and sensitive approaches to address these challenges. This study aims to review the effectiveness of various community-based nutrition interventions in preventing stunting and undernutrition among under-five children. A narrative review approach was employed to analyze six peer-reviewed articles published in the last five years (2021–2025), selected from PubMed, ScienceDirect, and Google Scholar using relevant keywords and inclusion criteria. The findings demonstrate that community-based nutrition interventions positively impact stunting reduction and improve child nutritional status. The most effective interventions included family-based nutrition education, growth monitoring, supplementary feeding, lipid-based nutrient supplementation, and innovative programs such as child-owned poultry. Active community participation, engagement of health cadres, and multi-sectoral collaboration were critical to the success of the programs. Community-based nutrition interventions are effective strategies to improve child nutrition and prevent stunting, particularly when implemented participatively and sustainably. These findings provide a basis for community nursing practices and the formulation of contextually appropriate and impactful nutrition policies.